2019
DOI: 10.1029/2018jc014746
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Model for the Baroclinic and Barotropic Ocean Response to Moving Tropical Cyclones: 1. Satellite Observations

Abstract: Changes of sea surface temperature and height, derived from 20‐day passive microwave and altimeter measurements for three tropical cyclones (TCs), Jimena, Ignacio and Kilo, during the 2015 Pacific hurricane season, sampling different stages of intensification, wind speeds, radii, Coriolis parameter, translation velocities, and ocean stratification conditions, are reported and analyzed. As triggered along the path of moving TCs, very large interior ocean displacements can occur to leave prominent sea surface he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, submesoscale features emerge or are magnified under calm conditions, especially just after a wind event has stirred the upper ocean, when the Ekman circulation interacts with the underlying mesoscale turbulence resulting in rich submesoscale structures. A special case of interest would be the study of hurricane wakes, which last several days after the pass of the cyclone [26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, submesoscale features emerge or are magnified under calm conditions, especially just after a wind event has stirred the upper ocean, when the Ekman circulation interacts with the underlying mesoscale turbulence resulting in rich submesoscale structures. A special case of interest would be the study of hurricane wakes, which last several days after the pass of the cyclone [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to Kudryavtsev et al. (2019), the OML thickness for a fast‐moving TC is approximately proportional to, hU10[Rmax/(NUh)]1/2 $h\sim {U}_{10}{[{R}_{\text{max}}/(N{U}_{h})]}^{1/2}$ where, N is the Brunt‐Väisälä frequency for the seasonal pycnocline, U 10 is ocean surface wind speed at 10‐m height, R max is the radius of maximum wind, and U h is the TC's translation speed. The wind‐driven current speed in the OML for a moving TC (Price, 1983) can be approximately expressed as UsτRmax/(hUh) ${U}_{\mathrm{s}}\sim \tau {R}_{\text{max}}/(h{U}_{h})$ where, τ is wind stress (τ=ρairCdU102 $\tau ={\rho }_{\text{air}}{C}_{d}{{U}_{10}}^{2}$) which can be estimated from air density ( ρ air ), drag coefficient ( C d ) and U 10 .…”
Section: Methods and Resultsmentioning
confidence: 99%
“…The observed ageostrophic current speeds are found to increase linearly with increasing wind speeds (20-50 m/s). According to Kudryavtsev et al (2019), the OML thickness for a fast-moving TC is approximately proportional to,…”
Section: Observed Near-surface Currents and Drift Ratios In Tcsmentioning
confidence: 99%
“…It has been observed that a TC can cause SSH depressions of up to 20–60 cm in satellite altimeter data (Ginis, 2002; Kudryavtsev et al, 2019), which has also been simulated in numerical ocean models (Shay et al, 1990). In spite of the strong near‐inertial contributions to these SSH depressions, geostrophic components, as shown in Figure 1, are also believed to be considerable.…”
Section: Introductionmentioning
confidence: 91%